Haematopoietic cytopenia associated with cyclin-dependent kinase 4/6 inhibitors: A real-world study of data from the food and drug administration adverse event reporting system database. (6th December 2022) - Ren, Xiayang; Yan, Cilin; Tian, Le; Cui, Xiangli
Objective: The haematopoietic cytopenia (HC) of the cyclin-dependent kinase (CDK)4/6 inhibitors was evaluated using the Food and Drug Administration Adverse Event Reporting System (FAERS). Method: Data from 1 January 2015 to 31 December 2021 has been retrieved from the FAERS database. Disproportionality analysis and Bayesian analysis were utilized in the data mining. The reporting odds ratio (ROR) with 95% confidence interval (CI) for HC was calculated for each CDK 4/6 inhibitor agent. Clinical features of the patients were collected and compared between death outcome and non-death outcome groups. Time to onset (TTO), proportion of deaths, life-threatening and hospitalizations of CDK 4/6 inhibitors-associated HC were also studied. Results: A total of 17, 235 cases of HC associated with CDK 4/6 inhibitors were identified with a median age of 65 years (interquartile range [IQR] 57–73). Palbociclib appeared the strongest signal, with the highest (ROR 9.64, 95% CI 9.46–9.83), followed by ribociclib (ROR 6.38, 95% CI 6.04–6.73) and then abemaciclib (ROR 2.72, 95% CI 2.49–2.97). Patients aged 18–64 had a higher proportion of deaths than those aged 65–84 (12.21% vs. 9.91%, p = 0.001). In Africa and Asia, the proportions of deaths were higher (31.65% and 26.13%, respectively). The median TTO was 26 days (IQR 14–65) for abemaciclib, 33 days (IQR 15–134) for palbociclib and 23 days (IQR 14–69) for ribociclib, respectively. The highest proportion of deaths, life-threatening and hospitalizations all occurred in abemaciclib (13.00%, 5.42% and 44.04%, respectively). Conclusions: Greater proportions of deaths occurred in Africa and Asia. HC may occur early in any CDK 4/6 inhibitor regimen. Abemaciclib had the highest proportion of deaths, life-threatening and hospitalizations. Health care workers should be more concerned about CDK 4/6 inhibitors. The higher proportions of serious events, including deaths, from Africa and Asia, as well as for abemaciclib, deserve further investigations through additional pharmacoepidemiological approaches.